Technology of development of future choir conductors’ professional competences: system-integrative approach - Shumska Liudmyla (State institution “South Ukrainian National Pedagogical University named after K D. Ushynsky”, 2020)
The article highlights the technology aimed at developing future choir conductors’ professional competences from the standpoint of the system-integrative approach in accordance with the requirements of new standards of higher education for bachelor students majoring in 025 "Musical Arts" in higher educational establishments. It determines the essence of the concepts "system" and "integration" in the context of higher school musical pedagogy as well as characterises the essence of implementation of the system-integrative approach in the process of conductorial-choral training by introducing into the educational process a specific pedagogical model which contains the components as follows: interdisciplinary-cognitive integration, methodical-operational integration, profession- and competence-based integration. It is established that the interdisciplinary-cognitive integration is a synthesis of knowledge units comprehended within special disciplines during the conductorial-choral training which form a new structural and substantive level of each separate discipline in the process of synthesis. It is noted that the methodological-operational integration acts at the intersection of a number of specific field methods dealing with the conductorial-choral disciplines and, as a result of polymodal accumulation of techniques, appears in the form of established professional methodological competences to be generalised, analysed and evaluated; they are based on their methodological knowledge and understanding of their further usage in the process of professional creativity. It is determined that the professional-competence integration is a strategic goal and the final result of the process of conductorial-choral training of the future bachelors: separate professional competences of the future choral conductors are integrated subsystems that jointly form a higher order system − the professional image of a choir conductor. The article systematises and organises professional competences of a future choir conductor, which are formed as a result of the proposed technology of their development on the basis of the system-integrative approach, and are considered as unconditional priorities of choral conductor's professionalism in the course of the polymorphic choir managerial and conductorial-pedagogical activities.